FACTORS OF THE FORMATION OF THE SAFETY OF ORGANIC COSMETIC PRODUCTS - YEMCHENKO, IRYNA; KOLDYUBA, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article indicates the factors that shape the quality and affect the safety of Ukrainian-made cosmetic products. According to the materials of the company «Hilary Cosmetics» LLC (Khmelnytskyi), the possibilities of increasing the production capacity of organic cosmetic products and their sale are considered. A confirmed guarantee of the quality and safety of the company’s products by providing consumers with an exclusive opportunity to exchange and return the product within 90 days from the moment of its purchase, in violation of the current legislation of Ukraine. According to the research data of TM «Hillary» products, it has been proven that the assortment corresponds to the development trends of the global and Ukrainian market of functional cosmetic products, and most of the products sold by «Hillary Cosmetics» LLC have no analogues in composition on the Ukrainian market. It is shown that the raw materials, labeling and safety indicators fully meet the requirements of the Technical Regulation on cosmetic products. The structure of the assortment of cosmetic products and the factors of formation of consumer properties were studied. The results of the conducted research showed that despite the presence of a wide range of high-quality, modern cosmetics of domestic origin on the market, Ukrainian consumers prefer products of foreign manufacturers. The authors stated that despite a significant amount of research in the field of technical regulation of the safety of cosmetic products, the issues of forming the safety of organic cosmetic products and the possibility of increasing the export potential of such products remain insufficiently covered. Monitoring studies on the market of organic cosmetics in Ukraine showed an almost complete absence of exports of domestic products, since Ukrainian organic cosmetics are still little known abroad. Research into the content of eco-certificates of Hillary Cosmetics products has determined that only natural components from leading manufacturers and suppliers of organic cosmetic ingredients from Italy, Spain, France, Germany, Denmark, the USA, etc. are used for its production.